Pneumonia caused by coagulase-positive methicillin-resistant Staphylococcus aureus - Lazović, Biljana; Dmitrović, Radmila; Simonović, Isidora; Jovičić, Nevena; Šarac, Sanja; Milić, Rade; Aleksić, Vuk (Vojnosanitetski pregled, 2023)
Introduction. Staphylococcus (S.) aureus is one of the most omnipresent and dangerous human pathogens, whose main characteristic is the production of the enzyme coagulase. This characteristic serves to identify and assess the patho-genicity of the bacteria. In addition to skin infections, endo-carditis, osteomyelitis, and infectious arthritis, it is a com-mon cause of pneumonia both in children and adults. Case report. We described a case of a 65-year-old woman with a dry cough and malaise with patchy areas of consolidation on the chest X-ray and “ground-glass” opacity with bronchial wall thickening and unilateral mediastinal lymphadenopathy on chest computed tomography imaging. Methicillin-resistant S. aureus was isolated from the bronchoalveolar as-pirate taken during bronchoscopy. The woman was empiri-cally treated with azithromycin, and later, based on the anti-biogram findings, azithromycin was replaced with mero-penem, after which her health improved. Conclusion. We presented a rare case of pneumonia with unconvincing symptomatology and laboratory and radiological findings. Paying more attention to such cases in the future is crucial, especially to the use of antibiotics to which staphylococci are increasingly developing resistance.